Pneumothorax, Giant Bullae and Bronchiectasis in Pediatric Patients with a History of Pulmonary TB - Arimbi, Muzaijadah Retno; Amori, Lakcandra Amar; Indrajanu, Intan Nurani; Nasrur Maulana, Eka; Tondi Winoto, Haryson (International Journal of Social Service and Research, 2025)
Pulmonary tuberculosis (TB) remains a major infectious disease in children, particularly in developing countries. Post-TB pulmonary complications, such as pneumothorax, giant bullae, and bronchiectasis, can significantly impair respiratory function over time. This case report highlights a 17-year-old girl with a history of BTA-positive pulmonary TB who developed pneumothorax, giant bullae, varicose bronchiectasis, and centrilobular emphysema. After completing OAT therapy in August 2024, she underwent VATS, bulectomy, and wedge resection due to persistent lung abnormalities. Thoracic CT imaging revealed extensive lung damage, including bronchiectasis and bullae. Currently, the patient is stable and asymptomatic. This case emphasizes the importance of early detection and comprehensive management of post-TB bronchiectasis in pediatric patients. Timely intervention can improve prognosis, especially given the high regenerative capacity of children's lungs. Early recognition of complications and appropriate treatment are crucial to prevent long-term respiratory impairment in children recovering from pulmonary TB.